Penggunaan Digital Berlebihan dan Kesejahteraan Subjektif pada Pegawai Negeri Sipil (PNS) - Nurliawati, Intan; Kadiyono, Anissa Lestari (Universitas Islam Indonesia, 2022)
Civil servants (PNS) are vulnerable to excessive digital use when doing their job in the COVID-19 pandemic situation, in fact it can have a negative impact on their well-being. Subjective well-being is very important to support the performance of civil servants to be optimal in the organization. However, studies that identify the relationship between the perceived digital overuse and the subjective well-being in civil servants have never been conducted in Indonesia. The purpose of this study was to obtain an overview about the relationship between the perceived digital overuse in general and its dimensions on the subjective well-being in civil servants. The participants of this study were 143 active civil servants who had worked for more than one year in one of the West Java Government Offices. Convenience sampling technique was applied by taking the entire population based on the researcher's criteria carried out as a representative of civil servants who were prone to showing perceived digital overuse during the implementation of Work From Home. This study used a simple regression method which was measured by the Perceived Digital Overuse Questionnaire (Gui & Büchi, 2021) and subjective well-being was measured by using the Warwick–Edinburgh Mental Well-Being Scale (Stewart-Brown et al., 2011). The results show that there is a negative relationship between perceived digital overuse and subjective well-being in civil servants. The dimension of overconsume is the most influential so that it can be a predictor factor on subjective well-being.